A critical innovation of photocatalytic degradation for toxic chemicals and pathogens in air - Truong, Phuoc Loc; Kidanemariam, Alemayehu; Park, Juhyun (Journal of industrial and engineering chemistry (Seoul, Korea), 2021)
[Display omitted] Air pollution by toxic chemicals and pathogens (bacteria, viruses, and fungi) has become one of the most critical problems worldwide because it has strong negative impacts on human health, both indoors and outdoors. Photocatalysis is a promising candidate to purify the atmosphere by removing pollutants among several physicochemical and biological methodologies. In this review, we discuss photocatalytic materials used for air purification, advanced methodologies for photocatalysts synthesis, and principles of photocatalytic nanoparticles that decompose pollutants, which include inorganic and organic compounds as well as dangerous pathogens. Recent achievements, outlook, and future directions in the field are discussed.